Exotic Psyllids and Exotic Hosts: Accumulation of Nonnative Psylloidea in North America (Hemiptera). (28th April 2021) - Horton, David R; Miliczky, Eugene; Waters, Timothy D; Burckhardt, Daniel; Halbert, Susan E
Abstract: The Psylloidea (Hemiptera) comprise 4, 000 species of small sap-feeding insects known as psyllids or jumping plant-lice. We summarize species composition of the nonnative psyllid fauna in North America and review detection records, current distributions, host use, life histories, and geographical sources. Forty-six species are considered to be nonnative accounting for 10% of the known North American psyllid fauna. The family Psyllidae is overrepresented in the pool of exotics (52% of exotic species) relative to global psyllid diversity, whereas Triozidae (at 11% of exotic species) is underrepresented. Records of initial detection range from the 1832 detection of a European pear psyllid to the 2016 detection of a Ficus specialist from Asia. Many species exhibit discontinuous distributions in North America presumably caused by multiple introductions or by secondary spread of established populations. Host plants of nonnative species are almost exclusively trees and shrubs. The factor most correlated with introduction is presence of hosts from the psyllid's native region. Virtually all host plants in North America have been imported intentionally for human-related use, with initial importation beginning in the 1500s and 1600s. Arrival of host plants in North America often preceded psyllid detection or arrival by decades or centuries. There has been almost no spillover by psyllids onto native plant species reflecting the narrow host range of Psylloidea. A glaring exception is the recent damaging colonization of a native Fraxinus closely related to the psyllid's European Fraxinus host. Biological and geographical traits correlated with arrival and establishment of nonnative psyllids have shifted through time. Temperate Europe was the source of the earliest arriving species, with initial detection records primarily in New England and eastern Canada. In contrast, recent arrivals are mostly Myrtaceae- and Fabaceae-feeding species from the Neotropics or Australia, with detection records limited mostly to Florida or California. Early-arriving, temperate zone species exhibit a formal winter diapause while recent arrivals from the Neotropics and Australia appear to reproduce more-or-less continuously.